OPTIMALISASI PENGEMBANGAN PRODUK PADA INDUSTRI RUMAHAN KOPI BUBUK CANGKIR EMAS DI DESA BATUNGSEL, KECAMATAN PUPUAN, KABUPATEN TABANAN - Manik Pratiwi, Anak Agung; Nararya Narottama; Ni Putu Decy Arwini (UNHI Press, 2025)
Batungsel Village in Pupuan District, Tabanan Regency, is renowned as a producer of robusta coffee. Processing coffee beans produces dried coffee beans (ose), roasted coffee, and ground coffee ready for sale. The problem faced by the Kopi Cangkir Emas home industry is that the entire manufacturing process still uses simple methods and tools. Product packaging is good, using plastic with a plastic press. This business has significant potential for greater production and new product development if supported by strategies to increase production, diversify products, and market them digitally, using food-grade machinery and environmentally friendly, recyclable packaging. By procuring coffee roasters and grinders, it is hoped that coffee powder production can be optimized and new products can be created through product diversification. Marketing Kopi Emas coffee products will also utilize digital marketing strategies to reach consumers and a wider market.